Temperature Dependence of Emission Properties of Self-Assembled InGaN Quantum Dots - 赵婉茹 翁国恩 梁明明 李增成 刘建平 张江勇 张保平 (Chinese physics letters, 2014)
Emission properties of self-assembled green-emitting InGaN quantum dots （QDs） grown on sapphire substrates by using metal organic chemical vapor deposition are studied by temperature-dependent photoluminescence （PL） measurements. As temperature increases （15-300K）, the PL peak energy shows an anomalous V-shaped （redshift blueshift） variation instead of an S-shaped （redshift-blueshift-redshift） variation, as observed typically in green-emitting InGaN/GaN multi-quantum wells （MOWs）. The PL full width at half maximum （FWHM） also shows a V-shaped （decrease-increase） variation. The temperature dependence of the PL peak energy and FWHM of QDs are well explained by a model similar to MOWs, in which carriers transferring in localized states play an important role, while the confinement energy of localized states in the QDs is significantly larger than that in MOWs. By analyzing the integrated PL intensity, the larger confinement energy of localized states in the QDs is estimated to be 105.9meV, which is well explained by taking into account the band-gap shrinkage and carrier thermalization with temperature. It is also found that the nonradiative combination centers in QD samples are much less than those in QW samples with the same In content.